Effect of a four-week ketogenic diet on exercise metabolism in CrossFit-trained athletes - Durkalec-Michalski, K.; Nowaczyk, P. M.; Siedzik, K. (Journal of the International Society of Sports Nutrition, 2019)
Background: The ketogenic diet is becoming a popular nutritional model among athletes. However, the relationship between its use and metabolism during exercise seems to have not been fully investigated. Methods: The aim of the study was to assess the effects of a four-week ketogenic diet (KD) on fat and carbohydrate (CHO) utilization during an incremental cycling test (ICT) in CrossFit-trained female (n = 11) and male (n = 11) athletes. During the ICT (while consuming the customary diet and after the KD), oxygen uptake and carbon dioxide exhalation were registered, and CHO and fat utilization as well as energy expenditure were calculated. Results: In males, the KD led to an increase in fat utilization (g·min- 1·kgFFM- 1 and % oxidation). It was particularly noticeable at exercise intensities up to 80% of VO2max. An increase in the area under the curve (AUC) was seen in males but not in females at up to =65% VO2max of fat utilization. Conclusions: Male CrossFit-trained athletes seem to be more prone to shifts in macronutrient utilization (in favor of fat utilization) during submaximal intensity exercise under a ketogenic diet than are female athletes.